Mathematical modelling of modified cell delineation strategy in packet switched networks - Kopeetsky, M.; Lin, A. (Mathematical Modelling and Analysis, 2006)
The paper proposes a new mathematical model of Cell Delineation (CD) strategy in any Packet Switching technology when Data Units (DUs) are of constant length. A special strategy that differentiates between synchronization failures and other channel errors with the sufficiently high confidence level has been proposed, analyzed and optimized. The mathematical analysis of the strategy is presented on the Asynchronous Transfer Mode (ATM) network example. The CD cycle implementation time is discussed and analyzed. The numerical results are presented for the case of the standard CD protocol.  First Published Online: 14 Oct 2010